Chemical composition and the insecticidal activity of Aeollanthus pubescens leaf essential oil against Anopheles gambiae sensu stricto - Tchobo, Fidèle Paul; DJOGBENOU, LUC SALAKO (My University, 2021)
Abstract Background: The excessive use of synthetic insecticides is responsible for many cases of resistance in insects. Therefore, the use of natural molecules of ecological interest with insecticidal properties is an alternative approach to the use of synthetic insecticides. The aim of this study is to investigating the larvicidal and adulticidal activity and the chemical composition of the essential oil of Aeollanthus pubescens on the major malaria vector, Anopheles gambiae. Methods: Three reference strains of Anopheles gambiae sensu stricto (Kisumu, Kiskdr and Acerkis) were used in this study. The leaves of A. pubescens were collected in southern Benin. The standard World Health Organisation (WHO) guidelines for larvicide evaluation were used, and the chemical composition of the essential oil was analysed by gas chromatography coupled to mass spectrometry. Adult mosquitoes of each strain were exposed to pieces of net coated with the essential oil for 3 min using the WHO cone bioassay method. Probit regression analysis was used to determine the concentrations that would kill 50 and 95% of each test population (LC50, LC95) and the knockdown time for 50 and 95% of each test population (KDT50, and KDT95). The difference between the mortality–dose regressions for the different strains was analysed using the likelihood ratio test (LRT). The log-rank test was performed to evaluate the difference in survival between the strains. Results: A total of 14 components were identified, accounting for 98.3% of total oil content. The major components were carvacrol (51.1%), thymyle acetate (14.0%) and ɣ-terpinene (10.6%). The essential oil showed larvicidal proper- ties on the Kisumu, Acerkis and Kiskdr strains, with LC50 of 29.6, 22.9 and 28.4 ppm, respectively. With pieces of netting treated at 165 μg/cm2, the KDT50 of both Acerkis (1.71 s; Z = 3.34, P < 0.001) and Kiskdr (2.67 s; Z = 3.49, P < 0.001) individuals were significantly lower than that of Kisumu (3.8 s). The lifespan of the three mosquito strains decreased to 1 day for Kisumu (χ2 = 99, df = 1, P < 0.001), 2 days for Acerkis (χ2 = 117, df = 1, P < 0.001) and 3 days for Kiskdr (χ2 = 96.9, df=1,P<0.001). Conclusion: Our findings show that A. pubescens essential oil has larvicide and adulticide properties against the malaria vector An. gambiae sensu stricto, suggesting that this essential oil may be a potential candidate for the control of the resistant malaria-transmitting vectors.
Keywords: Aeollanthus pubescens; Anopheles gambiae; Essential oil; Bioinsecticidal activity